AN INTERCONNECTION BETWEEN HEALTH AND JUSTICE IN THE ACCESS OF PEOPLE WITH MENTAL TRANSFORMS IN CONFLICT WITH A LAW IN THE CRIMINAL JUSTICE SYSTEM OF THE ESPÍRITO SANTO STATE - da Silva Campos, Bruno; Dettmann Wandekoken, Kallen; Costa-Moura, Renata; Santana da Silva, Geovana (LINKSCIENCEPLACE, 2026)
The present study is the result of a master’s degree research in psychology, whose objective is to carry out a dialogue between health and justice, as well as to produce data and reflections on the access of people with mental disorder in conflict with the law in the criminal justice system capixaba, conducted through the custody hearing. The mapping of this flow, comprised between May 2015 and December 2017, based on the methodology of intervention research and documentary analysis, indicates some relevant aspects: 1) Increasing the imprisonment of these people year by year; 2) The number of custody hearings held with people with mental disorder in conflict with the law, indicating how many have been held in custody and how many have received provisional release, as well as the number of recidivism; 3) The importance of the presence and performance of the psychosocial team within the custody hearing, composed of two psychologists and two social workers, in the recognition, unfolding and referrals of the cases. The conclusions pointed out by this study mainly highlight that the lack of investment in public mental health policies may be corroborating the increase in police capture to this public, instead of receiving help and being taken to health treatment, they become arrested and forgotten in prisons. The low (re) knowledge of mental health networks (RAPS and CAPS) by magistrates is also a worrying fact pointed out by this study.